Identifying The Students’ Motivation to Learn Writing - A, Arneli (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The attempt to identify the student’s motivation towards English has been extensively studied. However, identifying the students learning to write in relation to employment is scarcely conducted. In fact, writing skill has been postulated as the most challenging and rewarding skill to acquire future employment. The present study was conducted qualitatively. The reason for using qualitative was the limited time and sources that the researcher had. The sources of data were taken from the students who are currently studying in an English department, where the researcher is working as one of their English lecturers. There were 10 participants who were recruited randomly and voluntarily. The application of random sampling was aimed to allow the participants to freely and conveniently participate in the study. The instrument employed was an open-ended interview. The data analysed was the participants’ verbal responses delivered during the interviews. The finding indicated that learning to write was both important and challenging for them. With regard to the students’ future, learning to write was perceived important for students as they had to compete with the other university graduates to secure a decent employment. They thought that being an English graduate was not viewed from the way they communicate orally but more on the way to create formal impression through written media in which they are using to find jobs. Besides, the potential migration of the students to other English speaking countries is also perceived as the other primary reason for the student to acquire this skill. Since their motivation to learn English was instrumental and not integrative, despite planning to stay overseas, they considered that there were more aspects that should be done through writing rather than speaking. For instance, when dealing with documents and making reports they should rely on their writing skill rather than other skills.